INTEGRASI PERAN KELUARGA DAN SEKOLAH DALAM PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK USIA DINI - Ameily , Cantika Citra; Septiani, Dena; Hafizah, Dwi Fitri Nur; Zahra, Firra Fitria; Arianti, Sabrina; Irzalinda, Vivi; Anggraini, Gian Fitria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sexual violence against children is a serious issue that continues to increase and poses significant risks to children’s physical, psychological, and social development. Children are particularly vulnerable due to their limited understanding, dependence on adults, and lack of self-protection skills. Therefore, comprehensive and sustainable prevention efforts are required through the active involvement of families, schools, and the community. This paper aims to examine the forms of sexual violence against children and to analyze preventive strategies that can be implemented by the child’s immediate environment. The method used in this study is a literature review, drawing on various academic sources such as journals, books, and relevant legal regulations related to child sexual violence. The results of the review indicate that parental involvement in childcare, the provision of age-appropriate sex education from an early age, community awareness, and the role of schools in creating a safe and child-friendly environment play a crucial role in preventing sexual violence against children. The synergy between families, schools, and communities is essential to ensure that children can grow and develop optimally while being protected from sexual violence.